Pemodelan Metode Fuzzy Time Series Stevenson-Porter pada Nilai Peramalan Ekspor Non-Migas di Indonesia - Muhammad Rofiq Firdaus; Suwanda (UNISBA Press, 2023)
Abstract. Forecasting is the science of predicting events in the future, There are several kinds of methods used to project forecasting, since Zadeh's pioneering work in 1965, Fuzzy set theory has been applied to various fields. including Fuzzy Time Series, Fuzzy Time Series methods have been proven to improve classical forecasting methods such as handling data fluctuations, inappropriate environments, subjectivity uncertainty in data. By having the privilege of not requiring the fulfillment of special assumptions. This method was developed by Meredith Stevenson and John E. Porter. This research uses the